Relativistic Particles in Magnetized Media around Black Holes - Romero, Gustavo Esteban (2015)
We study non-thermal processes produced by the injection of relativistic particles in a strongly magnetized corona around an accreting black hole. The spectral energy distribution produced in this component of X-ray binaries can be strongly affected by different interactions between locally injected relativistic particles and the different fields of the source. We compute in a self-consistent way the effects of relativistic Bremsstrahlung, inverse Compton scattering, synchrotron radiation, and pair-production/annihilation of leptons, as well as of hadronic interactions. Our goal is to determine the non-thermal broadband radiative output of the corona. The set of coupled kinetic equations for electrons, positrons, protons and photons are solved and the resulting particle distributions are computed self-consistently. We apply our model to Cygnus X-1 obtaining a good fit of the observational data.